Oral emergency contraception practices of community pharmacies: a mystery caller study in the capital of Germany, Berlin - Gwenda Lungfiel; Franca Mandlmeier; Christian Kunow; Bernhard Langer (Taylor & Francis Group, 2023)
Abstract Background In Germany, oral emergency contraception (EC) with the active ingredients levonorgestrel (LNG) and ulipristal acetate (UPA) is available as over-the-counter (OTC) medicine only from community pharmacies (CPs). Because of the window of effect, which is limited to only a few days, CPs have a great responsibility to provide rapid and unimpeded access, while also ensuring "adequate" counseling. The aim was-for the first time in Europe and thus also in Germany for the methodology used in this study-to investigate immediate availability, pricing, and aspects of counseling. Methods Covert mystery calls were conducted in a random sample of CPs stratified by districts in the German capital Berlin. Each of the 263 CPs included was called once at random by one of two trained female student mystery callers. They simulated a product-based scenario for the UPA original ellaOne®, citing a contraceptive failure one day ago as the reason. Results Of 257 successfully called CPs, UPA preparations were immediately available in 98.4% (253/257) and LNG preparations in 86.8% (184/212) of CPs. Prices for UPA preparations varied from €15.95 to €42.95 (∆ 169%; median €35.00 [interquartile range (IQR) €5.91]) and for LNG preparations from €10.60 to €32.49 (Δ 207%; median €22.00 [IQR €5.76]). Information about the correct different window of effect of UPA and LNG preparations was provided in 69.8% (127/182) of CPs. UPA preparations were recommended in 63.1% (111/176) and LNG preparations in 17.2% (30/174) of CPs. Information was provided on how to take them as soon as possible in 30.8% (44/143) of CPs and on how to use them after vomiting in 46.0% (64/139). Conclusions Berlin CPs support access through high immediate availability, especially to UPA preparations. However, access is hampered by high absolute price ranges of both UPA and LNG preparations, which could ideally be minimized by a comparison app. It is positive that CPs promote the benefits of UPA preparations by recommending them noticeably more often than LNG preparations. However, there are deficiencies in giving advice, so there is a need to raise awareness among pharmacy staff to ensure "adequate" counseling in advance over the phone.